Political self-deception and epistemic vice. Issue 4 (4th December 2020) - Manson, Neil C.
ABSTRACT: Galeotti argues that we can gain a better understanding of political decision making by drawing upon the notion of self-deception and offers a rich articulation of what self-deception is, and how and why it exerts influence upon political decision making, especially in high-stakes contexts where the decision seems to be counter to rationality. But such contexts are also explicable from a different perspective, with different theoretical resources. In recent years the field of 'virtue epistemology' has discussed a wide range of epistemic vices – traits of character, and cognitive strategies, that stand in the way of gaining knowledge. This raises questions about how an explanation of political decision making in terms of self-deception relates to an explanation in terms of epistemic vice. Because the notion of epistemic vice applies to self-deception and to other cognitive deficiencies, it is argued that the broader notion of epistemic vice might be explanatorily richer, and more useful.